Alcoholysis of used cooking oil at high pressure using wasted catalyst obtained from crude oil processing pertamina unit III palembang - Ahmad Roni, Kiagus; Mardwita, Mardwita (International Journal of Engineering and Technology, 2019)
One of the possible methods to utilize used cooking oil is alcoholysis. Wasted solid catalyst obtained from Pertamina Unit III located in Palembang was used as catalyst. With this process some benefits might be obtained from these wastes. The alcoholysis of used cooking oil with ethanol and reactivated wasted solid catalyst at high pressure was conducted in an autoclave provided with manometer, thermometer, sampling device, heater, and mixer. The experiment was started by filling the autoclave with used cooking oil, alcohol, and catalyst, then the heater and the mixer were switched on. Samples were taken out at 10 minutes intervals, and after being separated, the bottom layer was analyzed in order to determine its glycerol content using acetin method. By raising the temperature, catalyst concentration, rate of mixing, and ethanol-oil ratio, the glyceride conversion increased. The alcoholysis of used cooking oil followed pseudo first order reaction with respect to the glyceride concentration. The relative favorable process conditions were 60 minutes of reaction time, temperature of 110Â°C, catalyst concentration of 2 %, mixing velocity of 310 rpm, and alcohol-oil ratio of 6 mgek/mgek. Under this condition the conversion was 70.09.Â Â